MODERNIZATION, ECLECTICISM, AND SAUDI ARABIA VISION 2030 ON FAMILY LAW: Positivization of Talaq Divorce in Niẓam Al-Aḥwāl 1443 H - Ni'ami, Mohammad Fauzan; Bawazier, Dio Alif; Ma’mun, Sukron (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Not bereft of the vision of 2030, Saudi Arabia reformed its Islamic family law, which resulted in the issuance of Niẓam al-Aḥwāl al-Syakhṣiyyah 1443 H. However, this modernization attempt is shadowed by the long-term preference for the established madhab. By focusing on the talaq issue, this article aims to investigate to what extent this Niẓam articulated with Hanbali madhab in managing divorce. As a normative study, data were collected by examining the primary resource, Niẓam al-Aḥwāl 1443. The result indicates that the positivization of divorce is primarily attributable to the Hanbali’s source of law. This (intra-doctrinal) positivization is intended to ensure legal certainty for the sake of this nation's modernization efforts. It affirms that the attempt in the private sector is in fact a manifestation of the 2030 political vision.[Tidak lepas dari visi 2030, Arab Saudi mereformasi hukum keluarga Islamnya, yang berujung pada keluarnya Niẓam al-Aḥwāl al-Syakhṣiyyah tahun 1443 H. Namun, upaya modernisasi ini terbayangi oleh preferensi jangka panjang terhadap madzhab yang telah mapan. Dengan berfokus pada masalah talak, artikel ini bertujuan untuk menyelidiki sejauh mana Niẓam ini berkaitan dengan madzhab Hanbali dalam mengatur perceraian. Sebagai kajian normatif, data dikumpulkan dengan mengkaji sumber primer, Niẓam al-Aḥwāl 1443. Hasilnya menunjukkan bahwa positivisasi talak terutama disebabkan oleh sumber hukum Hanbali. Positivisasi (intradoktrinal) ini dimaksudkan untuk menjamin kepastian hukum demi upaya modernisasi bangsa ini. Ditegaskan bahwa upaya di sektor swasta sebenarnya merupakan perwujudan dari visi politik 2030.]